Antimicrobial study of methanol crude extract of Pandanus amaryllifolius leaves against pathogenic bacteria / Fathin Nur’Ezzah Hishamuddin - Hishamuddin, Fathin Nur’Ezzah (2015)
Emergence and spread of antimicrobial resistant among pathogenic bacteria has become a global issue. Thus, to solve the problem, novel natural product as antimicrobial agents is required. Besides that, undesirable side effects of synthetic drugs also have changed the world attention to use natural product. Pandanus amaryllifolius Roxb is a fragrant plant that comes from a family of Pandanacea. Since ancient time, it has been used as traditional herb and also flavouring agents in cooking besides exhibit antioxidant, antiviral and anticancer abilities. However, limited antimicrobial study has done on the leaves. Therefore, this study was undertaken to investigate the antimicrobial activity of Pandanus amaryllifolius leaves against pathogenic bacteria and screening the presence of phytochemical compounds. 1000mg/ml concentration of leaves extract was tested against S. aureus(ATCC 43300), E. coli (ATCC 25922), P. mirabilis (ATCC 12453) and P.aeruginosa (ATCC 10145) by using disk diffusion method. Bacteria that show susceptible are subjected to MIC and MBC test. Result shows that leaves extract has antimicrobial activity against S. aureus (ATCC 43300) and P. mirabilis (ATCC12453) but resistant against E. coli (ATCC 25922) and P. aeruginosa (ATCC 10145).In addition, P. mirabilis (ATCC 12453) has greatest antimicrobial effect with MBC value of 500 mg/ml compared to 1000mg/ml MBC value for S. aureus (ATCC43300). The leaves extract also shown the presence of alkaloids, flavonoids, phenols, tannins, steroids, terpenoids, and carbohydrates compounds. Therefore, it can be concluded that, methanol extract of P. amaryllifolius leaves has potential as antimicrobial agent with the presence of phytochemical compound.